The Relationship Between Productivity Changes and Poverty in the United States - Hayes, K. J.; Slottje, D. J.; Nieswiadomy, M. L.; Wolff, E. N. (Journal of Income Distribution®, 1995)
This paper examines the relationship between poverty and changes in productivity and other macroeconomic variables. It is not assumed that the relationship is unidirectional from productivity to poverty. Specifically, the hypothesis is that there may be bi-directional causality between poverty and changes in productivity. The empirical results suggest that feedback does exist between productivity and poverty. The clear public policy implication is that measures intended to affect productivity growth or poverty must be designed simultaneously.